Ecosystem services linked to nature-based solutions for resilient and sustainable cities in India - Ahmad, Nadeem; Hassan, Quamrul (Frontiers in Water, 2025)
Rampant urbanization and undervaluing of the natural ecosystem have detrimental impacts on urban spaces – increased flooding risk, increased air and water pollution, water stress, resource inefficiency, loss of biodiversity, and increased risk of ill health. Climate change further exacerbates the adverse impacts of urbanization. Despite the importance of the natural ecosystem, the blue and green spaces of the cities in India have drastically decreased. The present study highlights the degrading natural ecosystem, the negative impacts, and the need for resilience in Indian cities. Eco-centric approaches like nature-based solutions (NBS) are closely related to sustainability and resilience, offering a more efficient and cost-effective approach to urban development than traditional approaches. The paper explores the concept of NBS, focusing on ecosystem services as a ‘living’ and ‘adaptable’ tool to make cities resilient and sustainable with many regional implementations. It also focuses on the role of NBS in achieving the United Nations’ Sustainable Development Goals (SDGs). The paper critically analyses the five notable NBS projects from different countries (USA, Canada, The Netherlands, China, and Australia) and further addresses the viabilities for NBS intervention in Indian cities. It is observed that the successful adaptation of NBS in urban development necessitates eco-centric policies, collaborative research, adaptive management practices, community engagement, and a strong emphasis on a multi-benefit approach. A proactive focus on ecosystem services is strongly recommended for Indian cities, which includes raising an understanding of the value of nature, introducing NBS at the planning stage, and encouraging investment in ecosystem-based approaches.